Soundwalking Through Time, Space, and Technologies (Taylor & Francis, 2023)
Jacek; Smolicki; Soundwalking; Space; Technologies; Through; Time
English
Keywords: Jacek; Smolicki; Soundwalking; Space; Technologies; Through; Time; thema EDItEUR::A The Arts::AV Music::AVX Music recording and reproduction; thema EDItEUR::S Sports and Active outdoor recreation::SZ Active outdoor pursuits::SZC Walking, hiking, trekking; thema EDItEUR::T Technology, Engineering, Agriculture, Industrial processes::TT Other technologies and applied sciences::TTA Acoustic and sound engineering